PHYTO-PHARMACOLOGICAL PROPERTIES OF SIDA CORDIFOLIA: A REVIEW OF FOLKLORE USE AND PHARMACOLOGICAL ACTIVITIES - Khurana, Navneet; Sharma, Neha; Patil, Shailendra; Gajbhiye, Asmita (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Plants have been considered to be useful as a medicine for treating different ailments and improving health conditions, since ancient times. The plants as herbal drugs lay down an important foundation of different, well recognized, ancient, and traditional healthcare systems in India as well as other parts of the world. In India, plants constitute an important and indispensable role in different ancient healthcare systems such as Ayurveda, Siddha, Unani, Naturopathy, and Homeopathy. In Ayurveda system of medicine, one of the Rasayana plants having a great medicinal importance is Sida cordifolia belonging to the family Malvaceae. It is an annual undershrub found throughout the tropical and subtropical regions of India. It has been used since ancient times for various ailments in Ayurveda system of medicine. It has numerous folklore uses in different pathological conditions. The plant also reported to possess a number of important pharmacological activities. The present review focused on all these folklore use of this herb along with its reported pharmacological activities. Keywords: Sida cordifolia, Ayurveda, Parkinson's disease, Analgesic, Anti-inflammatory.